2008
DOI: 10.2489/jswc.63.3.112
|View full text |Cite
|
Sign up to set email alerts
|

Satellite mapping of conservation tillage adoption in the Little River experimental watershed, Georgia

Abstract: Conservation tillage is a commonly adopted best management practice for improving soil quality and reducing erosion. However, there are currently no methods in place to monitor conservation tillage adoption at the watershed scale. The primary objective of this study was to evaluate the usefulness of Landsat TM data as a tool to depict conservation tillage in a small Coastal Plain watershed. Satellite imagery was used to calculate four commonly used indices: Normalized Difference Vegetation Index, Crop Residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The spectral profiles of the Landsat bands are as follows: Blue (0.45-0.52 ”m), Green (0.52-0.60 ”m), Red (0.63-0.69 ”m), NIR (0.77-0.90 ”m), SWIR1 (1.55-1.75 ”m), and SWIR2 (2.09-2.35 ”m), corresponding respectively to Landsat 8 (OLI) bands 2-7 or Landsat 7 (ETM+) bands 1-5, and 7. The indices included the Normalized Difference Indices 5 and 7 (NDI5 [29], NDI7 [29]), the Normalized Difference Senescent Vegetation Index (NDSVI [30]), Normalized Difference Tillage Index (NDTI [13]), the Simple Tillage Index (STI [13]), and the Modified Crop Residue Cover (mCRC) index [1,12]. (SWIR1 − Green)/(SWIR1 + Green) Sullivan et al [1,12] Four green vegetation indices were also tested for inclusion in the analysis, including the Normalized Difference Vegetation Index (NDVI) [31], Optimized Soil-Adjusted Vegetation Index (OSAVI) [32], Visible Atmospherically Resistant Index (VARI) [33], and the Green Vegetation Index (VIGreen) [34,35].…”
Section: Calculation Of Landsat Indices and Creation Of An Imagery Stackmentioning
confidence: 99%
“…The spectral profiles of the Landsat bands are as follows: Blue (0.45-0.52 ”m), Green (0.52-0.60 ”m), Red (0.63-0.69 ”m), NIR (0.77-0.90 ”m), SWIR1 (1.55-1.75 ”m), and SWIR2 (2.09-2.35 ”m), corresponding respectively to Landsat 8 (OLI) bands 2-7 or Landsat 7 (ETM+) bands 1-5, and 7. The indices included the Normalized Difference Indices 5 and 7 (NDI5 [29], NDI7 [29]), the Normalized Difference Senescent Vegetation Index (NDSVI [30]), Normalized Difference Tillage Index (NDTI [13]), the Simple Tillage Index (STI [13]), and the Modified Crop Residue Cover (mCRC) index [1,12]. (SWIR1 − Green)/(SWIR1 + Green) Sullivan et al [1,12] Four green vegetation indices were also tested for inclusion in the analysis, including the Normalized Difference Vegetation Index (NDVI) [31], Optimized Soil-Adjusted Vegetation Index (OSAVI) [32], Visible Atmospherically Resistant Index (VARI) [33], and the Green Vegetation Index (VIGreen) [34,35].…”
Section: Calculation Of Landsat Indices and Creation Of An Imagery Stackmentioning
confidence: 99%
“…Of these, the Normalized Difference Tillage Index (NDTI) (van Deventer et al 1997) was found to be the most effective (Serbin et al 2009b(Serbin et al , 2009a), but was not as effective as CAI, SINDRI, or LCA. In contrast, others concluded that these tillage indices were able to differentiate conventional and conservation tillage using logistic regression (Gowda et al 2001;Sullivan et al 2008;van Deventer et al 1997). Zheng et al (2012) found that these mixed results were caused by inattention to the significance of the temporal dimensions of applications of tillage practices.…”
mentioning
confidence: 83%
“…Most slopes were less than 5%, with some valley side slopes ranging from 5% to 15% (Bosch et al 2007). Land use in the watershed included agriculture (31%), pasture (10%), riparian forest (28%), upland forest (22%), and urban area (7%) (Sullivan et al 2008). The primary crops grown were row crops (cotton, corn, and peanut [Arachis hypogea L.]), and vegetables, typically without artificial drainage.…”
Section: Methodsmentioning
confidence: 99%